Cytotoxicity of Carvotacetones from Sphaeranthus africanus Against Cancer Cells and Their Potential to Induce Apoptosis - Tran, Huyen Thi; Kretschmer, Nadine; Huynh, Loi; Bauer, Rudolf (Planta Medica, 2023)
Three carvotacetones (1 – 3) isolated from Sphaeranthus africanus were screened in 60 cancer cell lines at the National Cancer Institute (NCI) within the Developmental Therapeutics Program (DTP). At the concentration of 10−5 M, compound 1 (3,5-diangeloyloxy-7-hydroxycarvotacetone) turned out to be the most active compound against ACHN and UO-31 renal cancer cell lines with growth percent values of − 100% (all cells dead). Compound 2 (3-angeloyloxy-5-[2″,3″-epoxy-2″-methylbutanoyloxy]-7-hydroxycarvotacetone) showed strong effects in SK-MEL-5 melanoma and ACHN renal cancer cells with inhibition values of 93% and 97%, respectively. Compound 3 (3-angeloyloxy-5-[3″-chloro-2″-hydroxy-2″-methylbutanoyloxy]-7-hydroxy-carvotacetone) exhibited a quite strong effect on renal cancer cells with a growth inhibitory effect of 96% against ACHN and UO-31 cells. When treated with five different concentrations of 1 (1 × 10−8, 1 × 10−7, 1 × 10−6, 1 × 10−5, and 1 × 10−4 M), HOP-92 cells were found to be most sensitive with GI50, TGI, and LC50 values of 0.17, 0.40, and 0.96 µM, respectively. When using the ApoTox-Glo triplex assay to evaluate the apoptosis inducing effects of seven carvotacetones isolated from S. africanus in CCRF-CEM cells, compounds 1 – 6 increased caspase-3/7 activity with 1, 2, and 4 (3-angeloyloxy-5,7-dihydroxycarvotacetone) exhibiting the highest activitiy, indicating induction of caspase-dependent apoptosis.
Keywords: Sphaeranthus africanus; Asteraceae; carvotacetone; NCI-60 cell lines; apoptosis